Peer Conformity Towards Adolescents Alcohol Consumption Behaviour in Jayapura City - Violita, Fajrin; Asriati; Pamangin, Lisda Oktavia Madu; Andimuntja, Natalia Paskawati; Izaac, Fransina Alfonsina; Nurdin, Muhammad Akbar (Miracle Journal of Public Health, 2025)
Adolescent alcohol consumption is an important and complex issue as it not only impacts health but also fuels risky sex, violence, and drug use. The purpose of this study was to determine the relationship between knowledge and peer conformity on alcohol consumption behavior among adolescents in Jayapura City. This type of research uses quantitative methods with a Cross-Sectional Study design. The total population was 2552 male students in 5 junior high schools and five high schools in Jayapura City, and the sample calculation obtained 343 respondents. The sampling technique used proportional stratified random sampling and primary data collection using a questionnaire. Statistical analysis using the Spearman Correlation Test. The results of the analysis were obtained from 343 adolescents; most respondents had knowledge in the good category, namely 200 respondents (58.3%), and as many as 273 respondents (79.6%) in the category of peer conformity, the majority of which were in the moderate category. The correlation test results of the relationship between knowledge factors and alcohol-drinking behavior in adolescents obtained a p-value of 0.032 with a value of r = 0.116. So, it means that there is a relationship between knowledge and adolescent drinking behavior, but the strength of the relationship is very weak, with a negative correlation. As for the peer conformity variable, the p-value is 0.227, meaning that there is no significant relationship between peer conformity and adolescent drinking behavior. Health agencies are advised to strengthen the PIK-R program in schools to prevent adolescent alcohol consumption.